R&D to commercialization – nanotechnology - Shamsul Harumain, Zakuan Azizi; Ahmad, Rezal Khairi (2018)
The reciprocal relationship between research development (R&D) and commercialization lies on its ability to compensate the needs of both parties. In today’s world, without having a strong commercialization aspect, millions of dollars spent on R&D would be pointless and futile. Nanotechnology is a continuation of R&D in advance technology that deals with nanoscale materials which has a strong potential in transforming economies and societies on a global scale. This fast emerging technology has already booked its place in the industry such as the production of graphene, a single-layer man-made material which has 200x more strength than normal steel and possess high conductive capacity important in the electronics sector. In NanoMalaysia Berhad, we champion nanotechnology’s R&D and commercialization as a single entity by bringing potential research products from academia or research institute into market by either by forming new companies or joint ventures with local or international collaborators. This will not just benefit the government’s economic growth in a long run, but will also help in creating more alternative career opportunities as an industrialist equipped with research degrees.